Analysis of ECG parameter dynamics which define fatigue and the functional state of athletes - Kairiukstiene, Z.; Poderiene, K.; Velicka, D.; Trinkunas, E.; Poderys, J. (Medicina dello Sport, 2020)
BACKGROUND: Physiology and sport science are interested in the link between the development of fatigue and exercise performance. This study tests the hypothesis that the inter-dynamics of changes in the ratio between the RR and JT intervals of ECG could be informative for defining the state of fatigue during exercising. METHODS: We used two studies to simulate various functional states and to identify the peculiarities of this interaction, and what could be useful for the precise evaluation of the functional state. Seventeen athletes participated in the first study and 12 in the second study. A bicycle ergometer test using a 12-lead ECG was recorded for later analysis. RESULTS: The first study showed that when the load was higher the difference between JT and RR intervals was also higher (P<0.05). The JT and RR did not intersect at the start of the test or throughout the test. At recovery velocity adaptation does not return to baseline value (P<0.05). The second study revealed that after a 50W, 100W and 150W workload, the RR interval outran the recovery of JT the interval, but after 200W the recovery of the JT interval was statistically higher than the recovery of the RR interval (P<0.05). After 50W, 100W and 150W, the workload at the recovery index velocity of adaption was negative compared to baseline values (P<0.05), but after 200W these values became positive (P<0.05). CONCLUSIONS: The study confirmed the hypothesis that the accumulated fatigue, caused by exercising can be evaluated by the analysis the dynamics of JT and RR intervals during the fast recovery phase.